2015
DOI: 10.1186/s12866-015-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence signatures of Listeria and Aeromonas species recovered from treated wastewater effluent and receiving surface water in Durban, South Africa

Abstract: BackgroundTreated wastewater effluent has been found to contain high levels of contaminants, including disease-causing bacteria such as Listeria and Aeromonas species. The aim of this study was to evaluate the antimicrobial resistance and virulence signatures of Listeria and Aeromonas spp. recovered from treated effluents of two wastewater treatment plants and receiving rivers in Durban, South Africa.MethodsA total of 100 Aeromonas spp. and 78 Listeria spp. were positively identified based on biochemical tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 61 publications
2
21
5
Order By: Relevance
“…A 100% prevalence of the actA gene, which stimulates actin polymerization and causes L. monocytogenes to spread in the host cells was observed in this study. This rate is quite higher than that observed in the study of [3] which is 95% and much more higher than that obtained in the studies of [55]. The prevalence of the hylA and plcB genes in the present study was 100%.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A 100% prevalence of the actA gene, which stimulates actin polymerization and causes L. monocytogenes to spread in the host cells was observed in this study. This rate is quite higher than that observed in the study of [3] which is 95% and much more higher than that obtained in the studies of [55]. The prevalence of the hylA and plcB genes in the present study was 100%.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study, plcA and iap which code for phospholipase and invasion-associated protein respectively, occurred in 100% of the isolates. This is also higher than the prevalence noticed in other studies [53,[55][56][57]. The variations in the prevalence of virulence markers detected in this study and that observed in other studies may be due to the differences in the origin or source of the isolates.…”
Section: Discussioncontrasting
confidence: 69%
“…These genera have often been reported as carriers of antibiotic resistance plasmids in either environmental or clinical settings, such as plasmid mediated carbapenem- and colistin-resistance in Proteus and Providencia isolates. Recent studies have demonstrated the high potential of Aeromonas in carrying multidrug-resistance plasmids [4446], and in transferring plasmids in various environmental communities [2325]. Given the ubiquitous presence of Aeromonas in aquatic environments [47,48], Aeromonas might play a significant role in facilitating transfer and maintenance of plasmid-mediated ARGs in environmental communities.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that Listeria species readily survive conventional wastewater treatment processes even after tertiary treatment [10,15]. With reports of inadequate removal of Listeria pathogens from wastewater from the developed world [10], it can be presumed that wastewater treatment plants in developing countries may be inefficient for the removal of these pathogens from wastewater effluents prior to discharge into the receiving water bodies.…”
Section: Introductionmentioning
confidence: 99%